Altrusim and Morals - Franzen, Winfried (Practica et Speculativa: Studies Offered to Professor Andrzej M. Kaniowski, 2022)
Concerning the relation between altruism and morals there are not only disputes about how to conceptualize altruism, but even arguments that something like genuine altruism does not exist at all. Questions and arguments of this type will be analyzed. Furthermore it is argued that all moral reasoning has to be based on the prerequisite of a certain – at least partly natural – protoaltruism. At the same time, however, it has to be taken into account that there are more things involved in morals than mere altruism. Included are some aspects from evolutionary psychology and anthropology.